2022
DOI: 10.3389/fgene.2022.921432
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to hydroxyurea use from the perspectives of providers, individuals with sickle cell disease, and families: Report from a U.S. regional collaborative

Abstract: Sickle cell disease (SCD) is an inherited blood disorder that affects about 100,000 people in the U.S., primarily Blacks/African-Americans. A multitude of complications negatively impacts quality of life. Hydroxyurea has been FDA approved since 1998 as a disease-modifying therapy for SCD, but is underutilized. Negative and uninformed perceptions of hydroxyurea and barriers to its use hinder adherence and promotion of the medication. As the largest real-world study to date that assessed hydroxyurea use for chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 68 publications
1
11
0
Order By: Relevance
“…Induction of fetal haemoglobin (HbF) with hydroxyurea is one of the mainstays of therapy and is received by 57.5% of paediatric and 49.7% of adult patients in the registry. This is comparable to the United States (US), where a multisite study ( n = 412) published in 2022 and analysing data from 2015 to 2017 reported hydroxyurea use in 56.3% of participants overall 12 . Landmark trials support its use, demonstrating a reduction in SCD‐related morbidity 13 and a significant improvement in survival 14 .…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Induction of fetal haemoglobin (HbF) with hydroxyurea is one of the mainstays of therapy and is received by 57.5% of paediatric and 49.7% of adult patients in the registry. This is comparable to the United States (US), where a multisite study ( n = 412) published in 2022 and analysing data from 2015 to 2017 reported hydroxyurea use in 56.3% of participants overall 12 . Landmark trials support its use, demonstrating a reduction in SCD‐related morbidity 13 and a significant improvement in survival 14 .…”
Section: Discussionsupporting
confidence: 55%
“…This is comparable to the United States (US), where a multisite study (n = 412) published in 2022 and analysing data from 2015 to 2017 reported hydroxyurea use in 56.3% of participants overall. 12 Landmark trials support its use, demonstrating a reduction in SCD-related morbidity 13 and a significant improvement in survival. 14 Recent UK guidelines recommend offering hydroxyurea to all paediatric patients aged 9-42 months with genotype HbSS/ Sbeta 0 and after the age of 42 months to patients of all ages in view of the reduction in mortality.…”
Section: Management Of Scd In Australian Centresmentioning
confidence: 99%
“…A U.S. regional collaborative report on barriers to hydroxyurea use from the perspectives of providers, individuals with sickle cell disease, and families found providers and patient/caregiver reports about hydroxyurea use were inconsistent with one another; adults 26 years and older were least likely to be on hydroxyurea; and the likelihood of being on hydroxyurea decreased with one or more barriers, they also found that, even for patients on hydroxyurea, challenges to taking the medicine at the right time and forgetting were crucial unintentional barriers to adherence. Intentional barriers such as worry about side effects and “tried and it did not work” were important barriers for young adults and adults [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Because hydroxyurea is given at home, it is essential that the patient and family understand the need for strict adherence and also that the care team is aware of social factors that may complicate the patient's ability to obtain and take their medication. [66][67][68] Continued TCD monitoring is necessary. Hydroxyurea appears to be safe for long-term use, but study of its secondary effects, such as infertility, is ongoing.…”
Section: Transfusion Complications and Iron Overloadmentioning
confidence: 99%